2017
DOI: 10.1002/acr.23258
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Weight Loss, and Cause‐Specific Mortality in Rheumatoid Arthritis

Abstract: Objective. To examine associations of body mass index (BMI) and weight loss with cause-specific mortality in rheumatoid arthritis (RA). Methods. A cohort of US veterans with RA was followed until death or through 2013. BMI was categorized as underweight, normal, overweight, and obese. Weight loss was calculated as the 1) annualized rate of change over the preceding 13 months, and 2) cumulative percent. Vital status and cause of death were obtained from the National Death Index. Multivariable competing-risks re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 30 publications
3
31
0
1
Order By: Relevance
“…It is unclear how generalizable these results might be to other contemporary populations. Overall, our results showing an association between severe weight loss and increased mortality are similar to the results of 2 prior studies investigating weight loss and mortality that were performed among mostly men with RA . We constructed the weight change period around the RA diagnosis as a time point that is relevant to all patients diagnosed with RA and chose the baseline period prior to RA diagnosis to protect against reverse causation with RA symptoms affecting the initial weight in patients with RA.…”
Section: Discussionsupporting
confidence: 82%
“…It is unclear how generalizable these results might be to other contemporary populations. Overall, our results showing an association between severe weight loss and increased mortality are similar to the results of 2 prior studies investigating weight loss and mortality that were performed among mostly men with RA . We constructed the weight change period around the RA diagnosis as a time point that is relevant to all patients diagnosed with RA and chose the baseline period prior to RA diagnosis to protect against reverse causation with RA symptoms affecting the initial weight in patients with RA.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, we maximized the opportunity to detect a difference between RA patients and non‐RA subjects for weight change and mortality risk. Prior studies used RA‐only cohorts, mostly with longstanding disease, so weight change was not necessarily related to RA and may have immediately preceded death . In our study, we found a similar magnitude of effect for the relative risk of weight change on mortality in both RA patients and comparators, so we believe the obesity paradox occurs similarly in these populations.…”
supporting
confidence: 72%
“…Although obesity is a recognized cardiovascular risk factor, an “obesity paradox” has been observed in rheumatoid arthritis whereby greater body mass is protective of cardiovascular disease mortality 85. Proposed hypotheses include the inadequacy of commonly used body composition measures, epidemiologic phenomena such as index event bias,86 confounding by comorbidity,85 and lack of consideration of weight trajectories 8788. Adiposity itself may contribute to systemic inflammation, insulin resistance, and cardiovascular disease risk through the release of adipokines or other pro-inflammatory mediators 8990919293…”
Section: Mechanisms Linking Rheumatoid Arthritis and Cardiovascular Dmentioning
confidence: 99%